Growth of three species of Paulownia in the Ecuadorian Littoral - Sigcha_Morales Franklin; JAVIER GARÓFALO; Diego Fabricio Campaña Cruz; Bernardo Navarrete; Ricardo Limongi (Manglar)
In Ecuador, the reduction of forests is evident, so it is necessary to evaluate fast-growing forest species that can meet growing demands, avoiding deforestation in areas where forests of the region are still maintained. The objective was to evaluate the growth of three species of the genus Paulownia in three localities of the Ecuadorian Coast as a medium-term alternative for productive and afforestation purposes. Diameter, height and volume were evaluated in three locations with two planting frames for three Paulownia species (Paulownia fortunei Hemsl; Paulownia elongata SYHu; Paulownia hibrido and a control (Gmelina arborea Roxb) with three replications. Data were recorded in the second year of planting. The Paulownia species were surpassed by G. arborea in the evaluated variables. In the humid tropics localities, there was no statistical difference between Paulownia species contrasting with the dry tropics locality in which P. eloganta in the 3 x 3 m plantation frame that presented the best values. Paulownia species did not exceed the control. The best results were achieved in the localities of Los Ríos and Santo Domingo; however, they should not be considered an alternative for productive purposes and afforestation in the humid tropics of Ecuador.